Triglyceride glucose-waist circumference as a predictor of mortality and subtypes of cardiovascular disease: a systematic review and meta-analysis - Mehrdad Rabiee Rad; Ghazal Ghasempour Dabaghi; Hossein Sadri; Bahar Darouei; Reza Amani-Beni; Sadegh Mazaheri-Tehrani (Diabetology & Metabolic Syndrome)
Abstract Background The significant burden of cardiovascular diseases underscores the necessity for identifying novel predictive markers that can forecast both cardiovascular diseases and mortality. In recent years, TyG-obesity-related parameters have gained special attention in this regard. This study aimed to assess the association between TyG-waist circumference (TyG-WC) and cardiovascular diseases and mortality. Methods A comprehensive search was performed in databases including PubMed, Scopus, and Web of Science from their inception until October 6, 2024. The key outcomes of interest included all-cause mortality, cardiovascular mortality, cardiovascular diseases, myocardial infarction, stroke, coronary artery diseases, peripheral artery diseases, and heart failure. The pooled risk ratio (RR) with corresponding 95% confidence intervals (CI) was calculated. Meta-analysis was carried out using StataMP 14.0. Results A total of 17 studies were included in the analysis. The number of participants ranged between 2,224 and 95,342. The meta-analysis revealed that TyG-WC is significantly associated with an increased risk of all-cause mortality, cardiovascular mortality, cardiovascular diseases, myocardial infarction, stroke, coronary artery diseases, and peripheral artery diseases. However, only one study addressed the relationship between TyG-WC and heart failure with a positive correlation. Conclusion This study indicates that TyG-WC could serve as a promising predictor of cardiovascular diseases, along with cardiovascular and all-cause mortality. Given its accessibility, TyG-WC may be a practical tool for screening purposes.